2018
DOI: 10.1177/1368430217740434
|View full text |Cite
|
Sign up to set email alerts
|

Identity-safe or threatening? Perceptions of women-targeted diversity initiatives

Abstract: Women remain underrepresented in high-paying and highly valued fields, especially science, technology, engineering, and math (STEM; National Science Foundation, 2016) and high-power leadership positions (Thomas et al., 2017). One popular strategy for recruiting, retaining, and advancing women in STEM and leadership focuses on providing professional development opportunities specifically targeted toward women, such as women in science and engineering programs, women's networking groups, and leadership developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 92 publications
(96 reference statements)
2
45
1
Order By: Relevance
“…The latest research shows, however, significant limitations of the proposed solutions concerning the fight against discrimination (Windscheid et al, 2017;Cundiff et al, 2018;Braun et al, 2017;McDonald et al, 2018). There are many cultural and organizational barriers for achieving equality of opportunity for women and increasing their presence in company management boards.…”
Section: The Methods Of Fighting Against Gender-related Discriminationmentioning
confidence: 99%
See 1 more Smart Citation
“…The latest research shows, however, significant limitations of the proposed solutions concerning the fight against discrimination (Windscheid et al, 2017;Cundiff et al, 2018;Braun et al, 2017;McDonald et al, 2018). There are many cultural and organizational barriers for achieving equality of opportunity for women and increasing their presence in company management boards.…”
Section: The Methods Of Fighting Against Gender-related Discriminationmentioning
confidence: 99%
“…Moreover, emphasizing the importance of just one gender is disadvantageous. Both men and women feel more comfortable when social programmes are targeted at all employees instead of just one chosen employee category (Cundiff et al, 2018). Thus the question arises whether imitating men by women is a good strategy (Braun et al, 2017).…”
Section: The Methods Of Fighting Against Gender-related Discriminationmentioning
confidence: 99%
“…The authors also discuss potential unintentional consequences different diversity initiatives can have. The unintended negative consequences of programs that aim to increase gender equality are also the focus of the paper by Cundiff, Sohee, and Cech (2018). They demonstrate that diversity initiatives that clearly target women rather than all employees lead to feelings of discomfort and concerns about being treated negatively and unfairly.…”
Section: Overview Of the Papers In This Special Issuementioning
confidence: 97%
“…As another example, a statement of inclusivity regarding sexual and gender diversity on a fitness gym's brochure led to greater intentions among (presumably heterosexual) women to join the gym than when the gym's advertising materials lacked sexual and gender diversity information (Cunningham & Melton, 2014). In addition to the transfer effect, some evidence suggested that the most promising diversity initiatives should be aimed at all employees (e.g., not only women employees) and organized by a collective (e.g., not only by A TAXONOMY OF IDENTITY SAFETY CUES 20 management) in order to work effectively (Cundiff et al, 2018). Taken together, diversity philosophies that are far-reaching may cue safety for multiple stigmatized groups.…”
Section: Cue 2: Diversity Philosophies and Programmingmentioning
confidence: 99%